URGENSI RESILIENSI DALAM MENGHADAPI LIMINALITAS BERDASARKAN KISAH PARA RASUL - Simarmata, Paden Leonard; Saragi Napitu, Marojahan (THEOSOPHIA: Jurnal Teologi dan Pendidikan Kristiani, 2025)
Abstract Liminal periods, the transitional phase between two stable states, are often marked by uncertainty, confusion, and identity crises. In the context of spiritual life, liminality is not only a challenge but also an opportunity for faith growth. This study highlights the importance of resilience—the ability to endure, recover, and move forward—as a faith response to times of transition, drawing on narratives in the book of Acts. Through an analysis of several key events, such as the waiting for the Holy Spirit, the persecution of the early church, the conversion of Saul, and the Jerusalem Council, it is clear that the disciples' resilience arose not from personal strength, but from the encouragement of the Holy Spirit and the strength of the community. This study affirms that resilience is a crucial element in both individual and collective faith journeys, especially when standing between what is past and what is future. Therefore, the church today is called to cultivate spiritual resilience to remain relevant and thrive in a changing world. In the book of Acts, resilience is manifested in the extraordinary perseverance of faith of the apostles and the early church in the face of pressure, persecution, and hardship in order to spread the gospel. This resilience is driven by the power of the Holy Spirit and a firm belief in God's plan of salvation.Abstrak Masa liminal, yaitu fase transisi antara dua keadaan yang stabil, sering kali diwarnai dengan ketidakpastian, kebingungan, dan krisis identitas. Dalam konteks kehidupan rohani, liminalitas bukan hanya tantangan, tetapi juga peluang bagi pertumbuhan iman. Kajian ini menyoroti pentingnya resiliensi – kemampuan untuk bertahan, pulih, dan terus melangkah maju-sebagai respons iman terhadap masa-masa transisi, dengan mengambil dasar dari narasi-narasi dalam kitab Kisah Para Rasul. Melalui analisis terhadap beberapa peristiwa penting seperti penantian Roh Kudus, penganiayaan gereja awal, pertobatan Saulus, dan Sidang Yerusalem, terlihat bahwa resiliensi para murid tidak lahir dari kekuatan pribadi, melainkan dari dorongan Roh Kudus dan kekuatan komunitas. Kajian ini menegaskan bahwa resiliensi merupakan elemen penting dalam perjalanan iman individu maupun kolektif, terutama ketika berada di antara apa yang lama dan yang akan datang. Dengan demikian, gereja masa kini dipanggil untuk membina resiliensi spiritual agar tetap relevan dan bertumbuh di tengah dunia yang terus berubah. Dalam kitab Kisah Para Rasul, resiliensi terwujud sebagai ketekunan iman yang luar biasa dari para rasul dan jemaat mula-mula dalam menghadapi berbagai tekanan, penganiayaan, dan kesulitan demi menyebarkan Injil. Ketahanan ini didorong oleh kuasa Roh Kudus dan keyakinan teguh akan rencana keselamatan Allah.